Simulation of Water Vapor Condensation in a Partly Closed Structure: The Influence of the External Conditions of Temperature and Humidity. (24th June 2013) - Batina, Jean; Peyrous, René
Abstract : Our aim is to determine the more significant parameters acting on the water vapor condensation in a partly closed structure, submitted to external constraints (temperature and humidity) which induce convective movements and thermal variations inside. These constraints locally lead to condensation of the water vapor, initially contained in the air of the volume and/or on the walls. The inside bottom wall is remained dry. Condensed water quantities depend on: (1) dimensions of the structure, (2) the air renewing and its hygrometry, and (3) the phase between thermal and hydrometric conditions. Peculiar conditions are needed to obtain a maximum of condensation.